Penerimaan Terhadap Sistem Pembayaran QRIS Berdasarkan Model TAM dan UTAUT 2 - Efendi Efendi; Albertus Kristiadi (Musamus Journal of Business & Management, 2022)
QRIS is a new payment system launched by Bank Indonesia to become a national standard digital payment instrument. This study aims to analyze the impact of implementing QRIS as a new payment system using the TAM model moderated by innovation. Sampling used non-probability sampling method and purposive sampling technique. Respondents are those who have previously made transactions using the QRIS system. Researchers for the number of samples using 200 respondents who have used the QRIS payment system. In conducting data analysis, the application used is SmartPLS 3.2.9. The results showed that perceived ease of use and attitude had an influence on perceived satisfaction with QRIS which was mediated by intention to use. In addition, perceived usefulness and risk had no effect on the perceived satisfaction of QRIS mediated by intention to use. Intention to use does not affect the perceived satisfaction of QRIS moderated by innovativeness. If the public already understands how the QRIS system works, it is hoped that they can use it more easily and provide benefits for digital transaction services. To increase the usefulness of QRIS, Bank Indonesia also needs to expand the QRIS system support service network so that people can use it as a digital transaction tool to meet their daily needs.